BEDA KENAIKAN KADAR HEMOGLOBIN MELALUI INTERVENSI MADU PADA REMAJA PUTERI - Supratiknyo Supratiknyo (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2014)
Women have a higher risk of developing anemia , especially in adolescence . Anemia give affect to decreased growth, reduced physical fitness , decreased enthusiasm for learning . This study aims to investigate the effect of honey consumption on the rise in hemoglobin levels in anemic girls in the hostel Ma'had Aly Salafi Islamic Boarding School of Salafiyah Syafi'iyah Sukorejo Situbondo 2014 .This research design using pre ekperiment design . Sample of 46 respondents who conform the inclusion criteria . Sampling technique is by proportional stratified random sampling . From the 46 respondents , all of them in the given consumption of honey . The data obtained were processed with SPSS 16 softwer. The Analysis of the data used is the Wilcoxon signed rank test trials .The results showed that most of the 25 (43,1%) of respondents in the criteria hemoglobin levels rise. While the calculation of the results of research data by using test